2020
DOI: 10.1038/s41598-020-67686-z
|View full text |Cite
|
Sign up to set email alerts
|

High throughput single cell analysis of mitochondrial heteroplasmy in mitochondrial diseases

Abstract: quent mutations associated with LHON. Variant m.15257G > A in the CYTB gene, which results in the change of aspartic acid from position 171 to asparagine, could be causative because the mutation was initially described as one of the primary mutations of LHON and associated with some mitochondrial diseases. Based on the sequencing data, both cell lines showed homoplasmy with mutated mtDNA at the abovementioned positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…We investigated heteroplasmy in single cells by using single-cell droplet digital PCR (sc-ddPCR) on day 12 in the protocol, which enabled multiplex detection for the presence or absence of a particular genotype in a cell (Fig. 2 c) 15 . This assay, the results of which were plotted in quadrant analysis format by using FlowJo software for FACS analysis, revealed that homoplasmic cells with either healthy or mutated mtDNA were present in 7S fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated heteroplasmy in single cells by using single-cell droplet digital PCR (sc-ddPCR) on day 12 in the protocol, which enabled multiplex detection for the presence or absence of a particular genotype in a cell (Fig. 2 c) 15 . This assay, the results of which were plotted in quadrant analysis format by using FlowJo software for FACS analysis, revealed that homoplasmic cells with either healthy or mutated mtDNA were present in 7S fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…As the clinical phenotypes of MELAS and MERRF correlate to the heteroplasmy level in muscle but not in blood 11 , there is heterogeneity in the heteroplasmy level between cells even in the same tissue or organ, from organ to organ in the same person 12 . The heterogeneity of mtDNA is divided into intracellular and intercellular heteroplasmy 13 , and a single-cell analysis in mitochondrial biology has just emerged for clinical samples 14 , 15 . Current knowledge on mitochondrial diseases has not resulted in the precise prediction and prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…One existing application is genetic mosaicism detection [18,20,28,29]. Other potential applications include monitoring of chimerism in patients after stem cell transplantation [30], analysis of mitochondrial heteroplasmy in mitochondrial diseases [31,32], rare microbe detection for microbiome pro ling [33] and con rmation of metagenomic sequencing results [34].…”
Section: Discussionmentioning
confidence: 99%
“…Modern methods have been developed to detect directly or indirectly heteroplasmy in single cells. Such methods include an initial step of single cell isolation or propagation which is followed by massive parallel sequencing [30][31][32]. These advanced methods identify heteroplasmy at the single cell level but they cannot distinguish yet between levels four and five.…”
Section: The Hierarchical Levels For Studying Heteroplasmymentioning
confidence: 99%